Between Poetry and Natural Science: The Representation of Organic Nature around 1800 (KULT_online, 2012)
Michael Bies' study investigates the interconnectedness of 'vivacious representation' as an aesthetic and poetological ideal on the one hand and the corresponding goal of analysing 'living nature' in the evolving natural sciences in the late 18th and early 19th century on the other. Through detailed readings of Kant’s critical writings, Goethe's essays on the study of nature, and Alexander von Humboldt's scientific publications, Bies is able to show how the relationship of the two ideals is acknowledged as a theoretical dilemma in Kant, and how representations of nature such as Goethe's and Humboldt's are aimed at their mediation and reconciliation in both theory and representational practice, while their eventual disjunction in later 19th century scientific discourse is already foreshadowed.